TRENDS IN THE DEVELOPMENT OF ESTRADA MUSIC ART IN UZBEKISTAN (SECOND HALF OF THE 20TH CENTURY – EARLY 21ST CENTURY) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The Pop music of Uzbekistan has undergone significant changes from the second half of the 20th century to the beginning of the 21st century. This article explores the harmony between national and modern elements, new styles of young artists, technological advancements, international relations, and socio-political themes. It analyzes the development of Uzbek Pop and its recognition on the global stage.